2022
DOI: 10.3389/fendo.2022.932488
|View full text |Cite
|
Sign up to set email alerts
|

Antiosteoporosis and bone protective effect of dieckol against glucocorticoid-induced osteoporosis in rats

Abstract: BackgroundGlucocorticoids (GCs) induce osteoporosis, which results in fractures in the bond, causing significant morbidity. In the conducted study, we examined the antiosteoporosis effect of dieckol against GC-induced osteoporosis in rats.MethodsSprague–Dawley (SD) rats were used for the current study and dexamethasone (2.5 mg/kg) induced osteoporosis in the rats that received the dieckol (test) and alendronate (standard) for 20 weeks. Bone turnover parameters, microCT, antioxidant, inflammatory cytokines, nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
4
10
0
Order By: Relevance
“…The level of RANKL's receptor and the existence of OPG, which prohibit RANKL binding to RANK, determine the cellular response to RANKL. 47 In this context, Wang et al 48 showed that dexamethasone injected in a dose of (2.5 mg/kg/day) for 5 days caused elevation in osteocalcin and TRACP levels, reduction of OPG level with an elevation of RANKL plasma level as confirmed in our results.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The level of RANKL's receptor and the existence of OPG, which prohibit RANKL binding to RANK, determine the cellular response to RANKL. 47 In this context, Wang et al 48 showed that dexamethasone injected in a dose of (2.5 mg/kg/day) for 5 days caused elevation in osteocalcin and TRACP levels, reduction of OPG level with an elevation of RANKL plasma level as confirmed in our results.…”
Section: Discussionsupporting
confidence: 87%
“…The level of RANKL's receptor and the existence of OPG, which prohibit RANKL binding to RANK, determine the cellular response to RANKL 47 . In this context, Wang et al 48 showed that dexamethasone injected in a dose of (2.5 mg/kg/day) for 5 days caused elevation in osteocalcin and TRACP levels, reduction of OPG level with an elevation of RANKL plasma level as confirmed in our results. Moreover, Bastawy et al 49 stated that prednisolone, given daily for 2 months, at a dose level of (4.05 mg/kg), caused elevated levels of ALP and TRACP with decreased immunohistochemical expression of OPG, the bone‐forming indicator and increased RANKL expression, and this was linked to prednisolone‐induced osteoporosis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…bisphosphonates and denosumab). [5] Nevertheless, most of the targeted therapies have limitations due to their serious adverse effects, such as stroke, musculoskeletal pain, nausea, hypercalcemia, and so forth. [2,5] Therefore, exploring a new generation of antiosteoporosis drugs with high efficacy but few side effects remains an urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…Current strategies for osteoporosis therapy include calcium administration, vitamin supplement, and estrogen receptor modulation, as well as medical treatments (e.g. bisphosphonates and denosumab) [5] . Nevertheless, most of the targeted therapies have limitations due to their serious adverse effects, such as stroke, musculoskeletal pain, nausea, hypercalcemia, and so forth [2, 5] .…”
Section: Introductionmentioning
confidence: 99%